Case of syngamosis in partridges of a backyard farm - ANDREOPOULOU (Μ. ΑΝΔΡΕΟΠΟΥΛΟΥ) M.; TSIOURIS (Β. ΤΣΙΟΥΡΗΣ) V.; GEORGOPOULOU (Ι. ΓΕΩΡΓΟΠΟΥΛΟΥ) I.; PAPADOPOULOS (Η.ΠΑΠΑΔΟΠΟΥΛΟΣ) E. (Journal of the Hellenic Veterinary Medical Society, 2017)
Sick and dead 2-months-old partridges (Alectoris chukar) were presented to the unit of Avian Medicine, Faculty of Veterinary Medicine, Aristotle University of Thessaloniki, Greece. The birds were reared at a specially constructed wire cage, which covered 600 m2 of the ground, including self-growing flora, in the region of Diavata, in the countryside of Thessaloniki. The farm consisted of young partridges, adult pheasants and wild passerines. Two months after placing the birds, 5 partridges were found dead. During the clinical examination of the submitted sick partridges, severe respiratory distress was observed, while some birds had anemic combs and others were breathing with open beaks and had their necks stretched. The necropsy revealed the presence of numerous gapeworms in the lumen of the trachea, forming the typical " Y" shape, since male and female Syngamus trachea are locked in copulation. The mucosa of trachea was, also, thickened, irritated and congested. No lesions to other organs were observed and the microbiological examination of liver, spleen and air-sacs samples was negative. Meanwhile, faecal samples were collected from the farm for parasitological examination. A sedimentation method was used and eggs of S. trachea were found. Syngamosis was determined to be the cause of the partridges’ death. The gapeworms are considered potentially dangerous, especially for backyard, game-birds and free-living birds, while the control of the disease is complicated. This fact, along with the selective appearance of the clinical signs and the mortality only in the partridges of the farm are the remarkable points discussed in this article.